2019
DOI: 10.1105/tpc.19.00406
|View full text |Cite|
|
Sign up to set email alerts
|

Posttranslational Modification of the NADP-Malic Enzyme Involved in C4 Photosynthesis Modulates the Enzymatic Activity during the Day

Abstract: Evolution of the C 4 photosynthetic pathway involved in some cases recruitment of housekeeping proteins through gene duplication and their further neofunctionalization. NADP-malic enzyme (ME), the most widespread C 4 decarboxylase, has increased its catalytic efficiency and acquired regulatory properties that allowed it to participate in the C 4 pathway. Here, we show that regulation of maize (Zea mays) C 4-NADP-ME activity is much more elaborate than previously thought. Using mass spectrometry, we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…Less consideration has been given to the plasticity of the C 4 pathways within a species. NADP-ME is strongly light regulated by light quality (Casati et al, 1998) and quantity (Hatch and Kagawa, 1976;Bellasio and Griffiths, 2014b), and by time of day, through phosphorylation, with its activity peaking at two hours after dawn and decreasing slowly throughout the day (Bovdilova et al, 2019). Leaves positioned lower in the canopy may not receive the quality and quantity of light to activate NADP-ME to the levels observed at the top of the canopy (Figure 4, Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Less consideration has been given to the plasticity of the C 4 pathways within a species. NADP-ME is strongly light regulated by light quality (Casati et al, 1998) and quantity (Hatch and Kagawa, 1976;Bellasio and Griffiths, 2014b), and by time of day, through phosphorylation, with its activity peaking at two hours after dawn and decreasing slowly throughout the day (Bovdilova et al, 2019). Leaves positioned lower in the canopy may not receive the quality and quantity of light to activate NADP-ME to the levels observed at the top of the canopy (Figure 4, Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Both enzymes are regulated in the same manner even when expressed within C 3 leaves ( Fukayama et al, 2001 ; Taniguchi et al, 2008 ). A recent study has shown that C 4 NADP-ME is also regulated in the light by reversible phosphorylation at Ser419 which is involved in the binding of NADP at the active site ( Bovdilova et al, 2019 ). In contrast, PEPC is regulated by both metabolite effectors and reversible phosphorylation, but the mechanisms of regulation in C 3 and C 4 leaves are different ( Vidal and Chollet, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trapping was performed at 2 µl/min on a Nano cHiPLC Trap column (Sciex 200 µm × 0.5 mm, ChromXP C18-CL, 3 µm, 120 Å) with 100% A for 10 min. The separation was performed at 300 nl/min, on a Nano cHiPLC column (Sciex 75 µm × 15 cm, ChromXP C18-CL, 3 µm, 120 Å) 40 . The gradient was as follows: 0-1 min, 5% B (0.1% formic acid in acetonitrile, Fisher Chemicals, Geel, Belgium); 1-46 min, 5-35% B; 46-48 min, 35-80% B; 48-54 min, 80% B; 54-57 min, 80-5% B; 57-75 min, 5% B.…”
Section: Statistical Analysis Statistical Analysis Was Performed Witmentioning
confidence: 99%
“…A UniProt reviewed database (20,413 entries, accessed on 08/01/2019) containing the sequences of the proteins from Human was used. The following search parameters were set: Iodoacetamide, as Cys alkylation; Trypsin, as digestion; TripleTOF 6600, as the Instrument; gel-based ID as Special factors; Biological modifications as ID focus; Search effort, as thorough; and an FDR analysis 40 . Only the proteins with Unused Protein Score above 1.3 and 95% confidence were considered.…”
Section: Statistical Analysis Statistical Analysis Was Performed Witmentioning
confidence: 99%